The psychosocial impact of home use medical devices - Thomson, Ross John (2017)
Recent increases in life expectancy, combined with the rise of chronic diseases, have led to a rise in the use of medical devices to monitor and treat illnesses in people’s homes. To date, however, little attention has been paid to understanding the impact that these devices have on the home environment, the users of these devices and their partners. This thesis presents three studies investigating the physical, personal and social issues faced by people using home medical devices.